Kidney transplantation from living donors with multiple renal arteries - Ertuğrul, Gökhan; Aydın, Çağatay (Journal of Surgery and Medicine, 2019)
Aim: Although better outcomes have been reported recently due to advances in surgical techniques, kidney artery variations are still important for good clinical results in transplantation. The aim of our study was to compare the clinical outcomes of grafts with one and two or more arteries. Methods: Between April 2014 and January 2019, 117 patients with live kidney transplantations were evaluated retrospectively with two groups. Group 1 consisted with one artery grafts and Group 2: two or more arteries. We were evaluated clinical outcomes between groups. Results: Among 117 recipients, there were two or more arteries in 13 cases (11.1 %). There was no significant deference between these two groups in terms of clinical outcomes during a median 27 (1-60) months of follow-up (P=0.62). Conclusion: It appears that the presence of renal grafts with two or more arteries may not be counted as a relative contraindication for renal transplantation.